Financial integration and economic growth: impact of renewable energy investments, technology transfer, and climate change on Europe and central Asian economies - Abdelmohsen A. Nassani; Muhammad Imran; Shiraz Khan; Khalid Zaman; Haroon ur Rashid Khan; Mohamed Haffar (Financial Innovation)
Abstract Financial integration plays an important role in fostering global economic growth. Energy demand, technology transfer, sustainable production, and climate change have emerged as key drivers of sustainable development. This study explores the influence of financial integration, bolstered by renewable energy-induced trade, industry-driven technology, and environmental concerns, on regional economic growth. This study analyzes a panel of 39 high- and upper-middle-income European and Central Asian countries in 2017–2021. Using a panel generalized method of moments estimator, we reveal an inverted U-shaped relationship between regional economic growth and carbon emissions. Moreover, renewable energy-induced trade contributes positively to regional growth while trade openness and technology transfer further enhance this growth. Industry-driven technology negatively impacts regional growth owing to inadequate financial integration. The absence of sustainable energy infrastructure and industrialization also negatively impacts regional growth. Our study underscores the importance of increasing financial integration to promote sustainable energy-driven trade openness and technology transfer in line with the United Nations’ sustainable development agenda.